The Effect of Supernatural Priming on Cheating Behaviour - Lin, Patrick K. F. (Religions, 2020)
Research has shown that the mental activation of concepts related to supernatural agents (e.g., God, ghost) is capable of altering one’s moral behaviours. Based on the supernatural monitoring hypothesis, two experiments were conducted to investigate the impact of priming on cheating behaviour using undergraduate participants from Singapore. The results of the first experiment showed that participants who were primed with the concepts of God and ghost via a word-scramble task cheated less in a mathematical task than participants exposed to neutral primes. The second experiment showed that the activation of God and ghost concepts via a supraliminal priming method reduced the participants’ cheating in a riddle game, even when the participants were informed that they would be rewarded monetarily for correctly answering the riddles. The results suggested that the mental activation of supernatural agents could reduce cheating behaviour regardless of the presence or absence of explicit belief in supernatural agents.